Carsten Roever: Teaching and Testing Second Language Pragmatics and Interaction — A Practical Guide - Qianqian Zhang (Journal of Linguistics and Communication Studies, 2024)
This book provides comprehensive guidance on teaching and assessing second language pragmatics and interaction. From theoretical foundations to practical methodologies, it offers valuable insights for educators and researchers. Covering topics such as context theory and pragmatic strategies, the book introduces various teaching methods, including role-play activities and dialogue interactions, to foster learners’ pragmatic skills. Additionally, it addresses effective pragmatic assessment design, ensuring objective evaluations. Overall, the book is a valuable resource for enhancing learners’ development in pragmatics and interaction.